A documentação da fé: fluxos, apropriações e enquadramentos de objetos votivos no Santuário Nacional de Aparecida - Souza, Bianca Gonçalves de [UNESP] (2012)
The thesis objective is to comprehend the constitution of the documentation of faith, which is localized in the National Sanctuary of Nossa Senhora da Conceição Aparecida, in the Paraíba river valley. Within a room dedicated to votive offerings (objects which are leaved as representation or proof of the received grace or miracle), they become documents of faith, testifying and presenting as proofs of received miracles by Nossa Senhora da Conceição Aparecida’s believers. In the first part, there is the presentation of the religious institution, the National Sanctuary, accompanied by the space and reach descriptions. The space attributes documental value to the object. In the first chapter is done a analysis of founders stories and the formation of consecrated places; the same chapter brings a hagiography’s study of the image of Mary, which was fished in 1717, taking up again the edification of the Old and the New basilicas and mentioning the assemblage of believers (romarias in Portuguese), which are traditional since the first devotions during the 19th Century. It is mentioned other sacred spaces and the religious tourism, which is strongly developed in this river Paraíba’s valley. In a second chapter, there are stories of priests belonged to Saint Afonso Maria de Ligório’s order (which founded in 1732, what shed light to the devotion’s care: these religious men, especially since the final of 19th Century, which they arrived in this Brazilian region, they were directly evolved with the edification and the characterization of this Marian sanctuary. In the end of this chapter it is possible to reflect about the participation of the media and the communication, in the formation of the religious and national project, which reinforces the maintenance of an ... (Complete abstract click electronic access below)